Women's recovery from anorexia nervosa: a systematic review and meta-synthesis of qualitative research. Issue 4 (4th July 2019) - Stockford, Clare; Stenfert Kroese, Biza; Beesley, Adam; Leung, Newman
ABSTRACT: Anorexia nervosa (AN) is a complex and challenging condition and recovery can be a slow and difficult process. Predicting factors remain largely unknown. This paper aims to systematically review qualitative studies which have investigated female service users' experiences of recovering from AN and carry out a meta-synthesis of the themes they identified. Meta-ethnography was used to select and synthesize the studies. Articles published between 2002 and 2017 were searched in PsycInfo, EMBASE, CINAHL and Medline. Studies were included if they explored recovery from AN using a qualitative methodology. The methodological quality of the studies was systematically and critically appraised. Fourteen studies were selected for inclusion. Common themes reported by participants describe the process of recovery from AN as dealing with a fragmented sense of self, a turning point where insight and commitment to recovery is developed, and, in recovery, a reclamation of self through meaningful relationships, rebuilding identity and self-acceptance. Recovery from AN is experienced as a complex psychological process with many contributing factors. Findings highlight the need to reconsider clinical practice and treatment provision to incorporate the psychological components of self-identity into recovery programs.